2009
DOI: 10.2135/cropsci2008.09.0541
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Matter Changes in Turfgrass Systems Affect Binding and Biodegradation of Simazine

Abstract: Concern about pesticide losses from maintained turfgrass areas led us to examine the fate of the triazine herbicide simazine in turfgrass systems and, specifically, interactions between simazine binding to soil organic matter and biodegradation. Soil samples were removed from turfgrass systems of different ages, placed in microcosms, conditioned as sterile or nonsterile, and exposed to 14C‐simazine. At seven sampling intervals, the soil was extracted and 14C was separated into three pools; bound, extractable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…Organic ma er binds metals (Jeong et al, 2007), inorganic nutrients (Danneberger et al, 1984;Kaiser et al, 2008;Kang et al, 2009), pesticides (Hurto and Turgeon, 1979;Balogh and Anderson, 1992;Dell et al, 1994;Lickfeldt and Branham, 1995;Cisar and Snyder, 1996;Raturi et al, 1997Raturi et al, , 2003Wu et al, 2002;Cummings et al, 2009;Hixson et al, 2009;Magri and Haith, 2009), organic compounds (Shih, 2007), and compounds such as tetracycline (Gu and Karthikeyan, 2008). In turn, OM can also be bound to soil minerals such as clays (Zhang et al, 2008;Kothawala et al, 2009).…”
Section: Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic ma er binds metals (Jeong et al, 2007), inorganic nutrients (Danneberger et al, 1984;Kaiser et al, 2008;Kang et al, 2009), pesticides (Hurto and Turgeon, 1979;Balogh and Anderson, 1992;Dell et al, 1994;Lickfeldt and Branham, 1995;Cisar and Snyder, 1996;Raturi et al, 1997Raturi et al, , 2003Wu et al, 2002;Cummings et al, 2009;Hixson et al, 2009;Magri and Haith, 2009), organic compounds (Shih, 2007), and compounds such as tetracycline (Gu and Karthikeyan, 2008). In turn, OM can also be bound to soil minerals such as clays (Zhang et al, 2008;Kothawala et al, 2009).…”
Section: Adsorptionmentioning
confidence: 99%
“…The Soil Science Society of America (2008, p. 39) defi nes microbial biomass as "the total mass of living microorganisms in a given volume or mass of soil, or as the total weight of all microorganisms in a particular environment." Organic ma er supports large amounts of microbial biomass (Mancino et al 1993;Kerek et al, 2002;Shi et al, 2006Shi et al, , 2007Hixson et al, 2009), which is an important determinant of the quantity and quality of soil organic ma er (SOM; Guggenberger et al, 1999). Kerek et al (2002) reported that the microbial biomass associated with particulate organic ma er (POM) in pu ing greens ranged from 27.7 to 124.5 nmol lipid-phosphorus g −1 soil, depending on the age of the green.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of a carrier solvent for an organic compound is usually based on the aqueous solubility (and stability) of the test substance and desired soil moisture content (Hixson et al 2009;Taylor-Lovell et al 2002). When the volume of water required to dissolve the test substance exceeds targeted soil moisture content, an organic delivery solvent is used instead (Chakraborty et al 1995;Kruger et al 1997;Reimer et al 2005), typically at a lesser volume than the desired water content.…”
Section: Introductionmentioning
confidence: 99%
“…이 뿐만 아니라 제초제 의 확산을 방지하고 생분해를 촉진시키며 (Hixson et al, 2009), 식물의 긍정적인 영향을 주는 토양 내 N2O의 발 생량을 증가시킨다 (Li et al, 2013). 이에 국내의 유기질 토양개량재와 관련된 연구는 주로 피트모스, 코이어 더 스트, 훈탄 (Lee et al, 2006;Shin et al, 2012), 동물성 유기질 개량재 (Koh et al, 2006), 미생물활성재제 (Jeon and Woo, 2005) ; surface soil (excavated soil at depth of 0-50 cm), S1CC; surface soil + soil organic amendment at a ratio of 6% (v/v), S2; subsoil(excavated soil at depth of 50-100 cm), S2CC; subsoil + soil organic amendment at a ratio of 6% (v/v) z Means followed by different letters indicate significant differences using Duncan's multiple range test at 5% level Jung and Thornton, 1996).…”
unclassified